Analisis Tingkat Kepuasan Pengunjung Desa Wisata Wiau Lapi Kecamatan Tareran Kabupaten Minahasa Selatan - Umbokahu, Eklesia; Rumagit, Grace Adonia Josefina; Tarore, Melissa Lady Gisela (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
Agrotourism is a tourism concept that utilizes natural potential which will produce tourists. As for a type of agro-tourism, tourist village with a concept of unique traditions from the community, or natural scenery, can be found in the Wiau Lapi Tourism Village. This study analyze the level of satisfaction from the visitors and identify the attributes of interest. This research was conducted from April to June 2023. The method used in this study was purposive sampling and accidental sampling, with the data used in the form of primary data and secondary data. The analytical methods used in this study are the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Results of this study indicate that the value of the CSI is 75.95 percent with the criteria of Satisfaction. As for the results of the IPA, identifying the leading variables in the form of the main tourism of Kulung-Kulung Waterfall, Tuunan Waterfall, Saguer Distillation, as well as the friendliness, alertness and knowledge of the officers. There are improvements that need to be made from the Wiau Lapi Tourism Village, such the location strategic, the infrastructure is still inadequate and there is a lack of attention to cleanliness